Adsorption and diffusion behavior of pure H2, and H2/CO2, H2/CH4 mixtures in sandstone-rich clay shale reservoirs: Insights from molecular dynamics simulations - Alankaa Al-Harbi (22137029) (2025)
Underground porous formations offer promising potential for hydrogen (H2) and carbon dioxide (CO2) storage, aiding the energy transition and decarbonization goals. Effective underground hydrogen storage (UHS) depends on selecting an appropriate cushion gas, typically CO2 or methane (CH4), to control pressure, minimize H2 loss, and enhance injectivity and productivity. This study uses molecular dynamics simulations to analyze the adsorption and diffusion behaviors of pure H2 and H2/CH4 and H2/CO2 mixtures in slit nanopores of kaolinite and silica with different surface morphologies under subsurface conditions. Kaolinite exhibited the lowest H2 diffusivity due to higher surface adsorption and interfacial gas density on its hydrophobic surface. In contrast, the Q2 silica morphology (ionized with Na and OH) showed reduced interfacial density and adsorption, enabling higher H2 diffusivity. CO2 had the strongest surface affinity and served as a more effective diffusion barrier than CH4 with 25 % cushion gas significantly reduced H2 mobility. Overall, kaolinite-rich caprocks offer better sealing efficiency, while silica-rich formations (resembling Q4 topology) may favor hydrogen accessibility and recovery during injection and production phases. These results underscore the influence of mineral type and cushion gas on hydrogen transport and confinement. Integrating these molecular-level insights with pore- and reservoir-scale models is essential for optimizing hydrogen recovery and ensuring long-term sealing in UHS operations. Other Information Published in: International Journal of Hydrogen Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijhydene.2025.151214